Gendered Vulnerabilities in Cyberspace: Cybercrime Against Women in India and Imperatives - Bat, Khushali (Journal of Social Science and Humanities, 2026)
The digital era has brought unprecedented changes in the society, opening new avenues for communication, business and education. The internet can be viewed as a double-edged sword on one hand it has made the world a global village and on the other hand it has given birth to various maladies that make the user vulnerable to various malicious activities, where the offender is concealed. Use of social media platforms have introduced various forms of cybercrime, with women being disproportionately affected. Being a victim of cybercrime could be the most traumatic experience for women especially in a country like India where society looks down upon women if their name is involved in matters which question their integrity. Women often shy away from reporting any instances of cybercrime because they fear defamation. Cybercrime affects women the most by subjecting them to mental and emotional stress, humiliation and depression. In India cybercrimes against women have escalated significantly, presenting unique challenges that require comprehensive strategies for mitigation and control. Proper digital awareness can help inculcate safe online working environment for women. In such a scenario the role of Government and NGOs to educate women about their rights and importance of reporting cyberattacks become significant. The Indian Penal Code includes sections which addresses cases related to sexual harassment against women. The Information Technology Act also has sections which addresses the same offences. Access to internet is fast becoming a necessity for the economic well-being and is increasingly viewed as a fundamental human right therefore, it becomes important to ensure that this digital space is safe and an empowering place for all especially women and girls.